2002
DOI: 10.1103/physrevc.66.034303
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofT=0two body matrix elements onM1and Gamow-Teller transitions: Isospin decomposition

Abstract: We perform calculations for M1 transitions and allowed Gamow Teller (GT) transitions in the even-even Titanium isotopes -44 Ti, 46 Ti, and 48 Ti. We first do calculations with the FPD6 interaction. Then to study the effect of T=0 matrix elements on the M1 and GT rates we introduce a second interaction in which all the T=0 matrix elements are set equal to zero and a third in which all the T=0 matrix elements are set to a constant. For the latter two interactions the T=1 matrix elements are the same as for FPD6.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This formula was also obtained in Ref. [14] and holds for both integer and half-integer value of j. In Appendix A, we present some explicit formulas of nine-j symbols with J = K = 2j or J = K = 2j − 1.…”
Section: J-paring Interactionsupporting
confidence: 56%
“…This formula was also obtained in Ref. [14] and holds for both integer and half-integer value of j. In Appendix A, we present some explicit formulas of nine-j symbols with J = K = 2j or J = K = 2j − 1.…”
Section: J-paring Interactionsupporting
confidence: 56%
“…The effects of T = 0 two body matrix elements on M 1 and Gamow-Teller transitions for 44 Ti, 46 Ti, and 48 Ti is reported in refs. [16,17]. In this work it was shown that transition rates were much more sensitive to the details of the T = 0 interaction.…”
Section: Introductionmentioning
confidence: 70%
“…The IS spin-triplet pairing correlations have been reported to play an important role in enhancing the GT strength near the ground states of daughter nuclei with mass N∼Z [11][12][13][14]. At the same time, the total sum rule of the GT strength is quenched by ground state correlations due to the IS pairing [15]. The IS paring is also found to be important to reduce 0νββ decay matrix elements [16].…”
Section: Introductionmentioning
confidence: 99%